Stroke in patients undergoing coronary angiography and percutaneous coronary intervention: incidence, predictors, outcome and therapeutic options. (October 2012) - Werner, Nicolas; Zahn, Ralf; Zeymer, Uwe
In the present day, coronary angiography and percutaneous coronary intervention are considered to be safe procedures with low complication rates in general. Nevertheless due to their widespread use and their application in a continually aging population known to carry a higher risk for complications, periprocedural stroke affects thousands of patients undergoing coronary angiography and percutaneous coronary intervention worldwide every year. Stroke is reported to occur in 0.05–0.1% of diagnostic cardiac catheterizations and in 0.18–0.44% of patients treated with percutaneous coronary intervention in clinical routine today. Despite all improvements in pharmacological and technical issues, the rate of stroke after cardiac catheterization has remained almost constant over the last 20 years of invasive cardiology of invasive and interventional cardiology, which is most probably due to the immutability of the majority of risk factors before cardiac procedures. An advanced age, arterial hypertension, diabetes mellitus, coronary angiography performed under emergency conditions, history of stroke, renal failure, the use of an intra-aortic balloon pump, congestive heart failure and interventions at bypass grafts have been identified as risk factors for periprocedural stroke in large registries. Due to exceedingly high rates of mortality and disability stroke after coronary angiography still has an enormous impact on the patient's prognosis and on quality of life. If patients survive this devastating complication, most of them suffer from persistent neurological deficits such as motor or speech disorders. For its low incidence and consecutively missing data from randomized clinical trials, an evidence-based treatment could not yet be established, and treatment options are generally based on case series and small studies only. Nevertheless, intra-arterial thrombolysis and mechanical embolectomy seem to be promising and relatively safe approaches in the treatment of periprocedural ischemic stroke. Further research by randomized trials and large registries are needed to validate its efficacy and safety.